TATA CARA PENGISIAN FORMULIR ANGSURAN PINJAMAN DAN KARTU PINJAMAN (BUMDES) (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
To carry out the procedure for filling out loan and loan card installment slips on BUMDes, a system is needed that can help in the savings and loan flow in the form of installment flowchart, and for this procedure provides guidance in managing complete customer data in the form and slip. So that the administrator can find out whether a program is feasible or not feasible to run.Financial aspects are aspects that are used to assess the company's finances as a whole. This aspect is just as important as other aspects, there are even some entrepreneurs who consider this aspect to be the most important to be analyzed because from this aspect it is clearly illustrated the matters relating to company profits, so that it is one of the very important aspects to be examined for its feasibility. Banking is always connected financially, and here it is clear that the savings and loan program is always related to finance.With the flowchat, forms, and financial reporting, of course, it will make it easier to run this program. Forms above are very clear that customers who will pay in installments can directly fill out the forms provided and for reporting, namely for archives held by BUMDes or BUMDes management, so it can be directly used or run.